Call for emergency action to limit global temperature increases, restore biodiversity, and protect health. Wealthy nations must do much more, much faster (Universitas Medica, 2021)
The UN General Assembly in September 2021 will bring countries together at a critical time for marshalling collective action to tackle the global environmental crisis. They will meet again at the biodiversity summit in Kunming, China, and the climate conference (COP26) in Glasgow, UK. Ahead of these pivotal meetings, we—the editors of health journals worldwide—call for urgent action to keep average global temperature increases below 1.5 °C, halt the destruction of nature, and protect health.